The assessment of radioactivity and radiological hazards in soils of Bolu province, Turkey. Issue 3 (3rd July 2019) - Dizman, Serdar; Görür, Filiz Korkmaz; Keser, Recep; Görür, Osman
Abstract: The radioactivity levels in soil samples of Bolu province of north-western Turkey have been determined. There has been no information about radioactivity measurement reported in soil samples in Bolu province so far. For this reason, the activity concentrations of natural and artificial radionuclides ( 226 Ra, 232 Th, 40 K, and 137 Cs) were measured in soil samples collected from 40 different points in Bolu province of north-western Turkey using gamma spectrometry technique with a high-purity germanium detector. The average activity concentrations (range) of 226 Ra, 232 Th, 40 K, and 137 Cs were found to be 18.2 (3.8–49.9) Bq/kg, 17.3 (4.1–37.9) Bq/kg, 258.3 (64.6–518.9) Bq/kg, and 7.5 (0.6–43.6) Bq/kg, respectively. At the end of the analysis, the radioactivity values were lower than the world average values reported by United Nations Scientific Committee on Effects of Atomic Radiation (UNSCEAR). In order to evaluate the radiological hazards resulting from natural radioactivity, radium equivalent activity (Raeq ), gamma index (Iγ ), external hazard index (Hex ), absorbed dose rate in air (D), annual gonadal dose rate (AGDE), the annual effective dose rate (AEDE), and excess life time cancer risk (ELCR) were calculated and found in the range of 14.8–129.8 Bq/kg, 0.1–0.5, 0.0–0.4, 7.0–60.2 nGy/h, 49.8–417.5 µSv/y, 8.6–73.8 µSv/y, and 0.3 × 10 −4 to 2.6 × 10 −4, respectively. These results were compared with recommended values (370 Bq/kg for Raeq, <1 for Iγ, <1 for Hex, 55 nGy/h for D, 300 µSv/y for AGDE, 70 µSv/y for AEDE, and 2.9 × 10 −4 for ELCR) by European Commission (EC), UNSCEAR and International Commission on Radiological Protection (ICRP). As a result, health hazards originated by natural radiation from soil samples of the Bolu province is low and insignificant.